Effect of Cycocel Concentration on Result of Mini Potato Tubers (Solanum tuberosum L.) in Hydroponic Substrate - haris wijaya (Universitas Trunojoyo Madura, 2017)
This study aimed to determine the effect of cycocel on mini potato tuber yield at various concentrations. Preparation of potato planet has done at plant tissue culture laboratory ,Faculty of Agriculture, University of Jember, in February-April 2016 and field experiments was carried out at Jampit Village, District Sempol, Bondowoso, May to September 2016. The research method used is Complete Random Design (RAL) single factor. Factor concentration of cycocel consisting of five levels, namely: 0 ppm (C0), 500 ppm (C1), 1000 ppm (C2), 1500 ppm (C3), and 2000 ppm (C4), with six replications. The results showed that the plant which treated by cycocel 2000 ppm has a shorter plant height of 27.40 cm, lower plant fresh weight 35.62 grams, and the higher number of tubers15,83 compared to the others factors. On the other variables cycocel no significant effect, on number of stems and total weight of tubers per plant.